Labor productivity in the middle income trap and the graduated countries - Gokhan Yılmaz (Central Bank Review (CBR), 2016)
In this paper, we investigate the role of labor productivity growth and whether the determinants of labor productivity growth differed among the middle income trap (MIT) and the graduated (non-middle income trap, NMIT) countries in the 1950–2005 period. We decompose labor productivity growth into "within sector" productivity improvements, "static structural change" productivity progress and "dynamic structural change" gains. Moreover, we study sectoral contributions to within sector productivity gains in these countries. We find that there was a significant labor productivity growth rate difference between the MIT and the NMIT countries, and this difference mainly originated from the within sector productivity improvements. Our sectoral analysis reveals that the most important sector that enlarged the within sector productivity growth gap between the MIT and the NMIT countries was manufacturing.
Keywords: O11; O40; O47; 330; Economic growth; Productivity; Structural change; Middle income trap